Key aspects of integration of strategic planning in marketing with project management - Oleksiienko, Roman; Skorupych, Artem; Volodina, Daryna (Herald of Economics, 2024)
Introduction. Today, strategic marketing plays a key role in ensuring the long-term competitiveness of enterprises by implementing projects with increasingly limited resources and increased requirements. However, due to the constant scientific and technological progress and fierce competition, there is a need for monitoring and timely adaptation to innovative methods of doing business. It is project management that has recently become the cornerstone of success in the activities of most foreign and partially domestic enterprises due to its technological methodology. The purpose of the study is to develop a concept for integrating the key area of strategic marketing for enterprises with innovative project management to achieve long- term competitiveness. Research methods. In order to deepen both areas of activity and create a comprehensive, systematic integration concept, a detailed literature review was carried out, our own previous scientific developments were analyzed, logical thinking and situation modeling were applied. Results. As a result, it was found that both areas can be harmoniously combined in the form of a strategy that directs activities in the right direction to achieve the goal in the best way, and tactics that ensure that projects are executed accurately in accordance with the established requirements for quality, speed and quantity. Key aspects of integration were identified and stages of integrated activities were developed, which together are of practical interest. The concept achieves a synergistic effect, which consists in understanding the areas of responsibility, calculability, compliance of projects with the established requirements, flexibility, innovation, and improved control. Prospects. Taking into account the achievements of scientists, it is concluded that almost no attention has been paid to the practical integration of project management into marketing. In this regard, there is a need to study the practical application of the developed concept through case studies and to establish real indicators of business performance.